PREVALENCE OF SARCOPENIA IN ELDERLY PATIENTS ON HEMODIALYSIS. - Fernando Lamarca; Juliana Rodrigues; Renata Fetter; Fernanda Bigogno; Maria Kamimura; Flavia Baria; Lilian Cuppari (The Korean Society of Nephrology, 2012)
Sarcopenia is strongly associated to aging and can be defined as a decrease in muscle mass, strength and muscle quality. Hemodialysis (HD) patients are exposed to several factors that lead to a loss of muscle mass, which in turn can accelerate the development of sarcopenia. We aimed to evaluate the prevalence of sarcopenia and to compare the nutritional and inflammatory profile of sarcopenic and non-sarcopenic elderly patients on HD. Seventy-four elderly patients on HD (68.9% male; age: 69.3 ±6.4 years) were included. Sarcopenia was defined by a handgrip strength (HGS) <10th percentile of a Brazilian population-based reference study. Obesity was defined as body fat % (sum of skinfold thicknesses) above the median values for men (≥26%) and women (≥39%); abdominal obesity as waist circumference ≥102 cm in men and ≥88 in women and inflammation (ultra sensitive C-reactive protein -CRP) as CRP ≥10 mg/L. Sarcopenia was observed in 41% of the patients. No significant difference was observed between Sarcopenic (n= 30; Male 67%; Age 69 ±6.2 years; BMI 24.5 ±4.9 kg/m2) and non-sarcopenic (n= 44; Male 73%; Age 69.7 ±6.6 years; BMI: 26.2 ±4.5 kg/m2) groups, as shown below: Sarcopenic Group (n= 30) Non-Sarcopenic Group (n= 44) Diabetes (n; %) 12 (40) 13 (30) Obesity (n; %) 13 (43) 24 (55) Abdominal Obesity (n; %) 10 (33) 21 (48) Inflammation (n; %) 8 (27) 9 (20) In conclusion, sarcopenia is highly prevalent in elderly HD patients and the inflammatory profile of sarcopenic and non-sarcopenic patients is similar. In addition, these results show that sarcopenia does not exclude the occurrence of increased adiposity, as shown by the elevated frequency of obesity and abdominal obesity in the elderly sarcopenic group.